Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru - Grados, Juan (Zootaxa, 2018)
Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) are described. Aphyle niedmandi sp. nov., Evius ocassus sp. nov., Paranerita maculata sandeepani ssp. nov., Paranerita kotolnuki sp. nov. and Baritius flexuosus sp. nov. were collected in the Tambopata River region, Madre de Dios (Peru), as part of a Citizen Science Project, in mutual collaboration between the Natural History Museum (Lima–Peru) and Rainforest Expeditions. External morphological descriptions, morphology of male genitalia, and geographic distributions in Peru are given for all taxa as well as their barcoding.